Mbecek Culture in Religious and Social Perspectives in Ponorogo Regency, East Java - Ahmad Muslich (Al-Hayat: Journal of Islamic Education, 2020)
This study aims to determine the early history of the mbecek culture and people's views of the mbecek culture in terms of religious, social and cultural perspectives. An exciting aspect of this research is that the culture of mbecek has become a tradition for generations. The culture which initially originated from values originating from the religion and culture of the nation began to shift costs that lead to the benefits of materialism, business and economy. Data collection is done by way of interviews with government leaders, religious leaders, community leaders, educational leaders and cultural actors. From the results of the study, it can conclude that the culture of birth based on religious, social and cultural values of the Indonesian people. In a spiritual perspective, religious leaders are of the view that the mbecek tradition needs to preserved on condition that it does not deviate from ethical values or teachings. In the socio-cultural perspective, community leaders are of the view that mbecek culture is an implementation of the realization that humans cannot live alone and need help from others. Mbecek culture is part of the values of cooperation or assistance in social life.